A Preliminary Study of the Changing Role of the State Towards the China Model (1978 – 2023) - Yahya, Siti Hasmah; Daud, Sity; Mohd Huda, Mohd Ikbal (Business and Economic Research, 2024)
The article is a preliminary study of the changing role of the state towards the China Model (1978 – 2023) by tracing the economic development phases since the reform and opening-up programme and state intervention in their development agenda. The state has played many roles, notably political, social, and economic ones. However, the focus of this paper is more on the role of political-economic development. This paper is an explorative study of the main characteristics of China’s economic development in the different phases and recognizes the role of the state in China’s economic development through qualitative debates and analyses as an evidence of state intervention from 1978 towards the China Model in 2023.